ANALISIS KOMPARATIF LAPORAN KEBERLANJUTAN PERUSAHAAN PERTAMBANGAN PADA KATEGORI EKONOMI (SERI 200) SESUAI STANDAR GLOBAL REPORTING INITIATIVE - Makherta Sutadji, Ika; Saraswati, Wiwik; Indriastuty, Nina (Jurnal GeoEkonomi, 2024)
This research aims to analyze and compare sustainability reports disclosed by mining companies listed  on the Indonesia Stock Exchange in the oil and gas production and refinery sub-sector. By using GRI  (Global Reporting Initiative) standard guidelines, This research uses the economic category (series  200) as a specific topic focus. The type of research is descriptive-qualitative, with content analysis  techniques and comparative methods. The research results show that from the specific topics raised by  six companies based on the subsector, six companies were listed. There are 2 companies that, upon  accessing the company website, do not report sustainability reports, namely PT. Sugih Energy Tbk SUGI and PT. Super Energy Tbk-SURE. Sustainability Reports were prepared by 4 companies referring  to POJK Standards, namely PT. Astrindo Nusantara Infrastruktur Tbk-BIPI, PT. Energi Mega Persada  Tbk-ENRG, PT. Medco Energi Internasional Tbk-MEDC, and PT. Mitra Investindo Tbk-MITI.  And PT refers to the GRI Standards. Energi Mega Persada Tbk-ENRG and PT. Mitra Investindo Tbk MITI and PT. Medco Energi Internasional Tbk-MEDC. Level of disclosure of specific topics at PT.  Mitra Investindo Tbk-MITI by 29% and PT. Energi Mega Persada Tbk-ENRG by 50% and PT. Medco Energi Internasional Tbk-MEDC by 57%. This indicates that there are still many companies that do  not refer to the GRI Standards because of their voluntary nature in making sustainability reports. Not  all disclosures based on the GRI Standards have been disclosed, so the percentage results are still not  high enough. Based on the results of this research, it is hoped that companies can make better and more  complete sustainability reports that refer to the GRI Standards in the coming year